KNOWLEDGE AND ATTITUDE TOWARDS CARDIOVASCULAR DISEASE AND ITS RISK FACTORS AMONG THE SAUDI POPULATION: A CROSS-SECTIONAL SURVEY (CAHIERS MAGELLANES-NS, 2024)
Background: Cardiovascular diseases (CVDs) pose a significant health threat globally, particularly in developing nations like Saudi Arabia. Research indicates that 42% of deaths in Saudi Arabia are associated with CVD, and awareness of its risk factors among the population is alarmingly low. This study aimed to assess the knowledge and attitudes regarding cardiovascular diseases and their risk factors among the Saudi population to address the critical knowledge gaps identified in previous research.Methods: A cross-sectional survey was conducted from July to November 2024, involving Saudi adults over the age of 18. Participants were recruited through a random sampling procedure via various online platforms. A structured questionnaire, designed to evaluate awareness and attitudes towards CVD and its risk factors, was administered. Data analysis included demographic profiling and comparison of knowledge and attitude levels among respondents. Results: A total of 1,202 participants were surveyed, predominantly female (76.4%), with a mean age of 28.9 years. The majority (93.8%) recognized smoking as a CVD risk factor; however, only 14.8% correctly identified reduced physical activity as a risk. Awareness regarding obesity's association with CVD was high (96.0%), yet 83.4% misunderstood the implications of irregular eating habits. Symptoms of CVD showed varied recognition; 78.2% identified palpitations, while only 39.4% acknowledged excessive sweating as significant. Notably, 84.5% exhibited a positive attitude towards cardiovascular health, supporting regular physical activity and smoking cessation.Conclusion: This study highlights significant gaps in knowledge about CVD risk factors within the Saudi population, despite a generally positive attitude towards healthy lifestyle practices. There is an urgent need for targeted educational interventions to improve awareness, particularly regarding lifestyle risk factors and less recognized symptoms of CVD. Enhanced public health strategies could mitigate the rising burden of cardiovascular disease in Saudi Arabia.